THE USHNOS: COMMUNICATING RIVER BASIN IN WARPA AND TOROBAMBA, AYACUCHO - Valdez Cárdenas, Julio Ernesto (2014)
In the present article the existence of architectonic structures of Ushnos located in the part north of the department of Ayacucho, within the political demarcation of the provinces of Huanta and The Sea, where Warpa and Torobamba find the basins of the rivers respectively shows up. You show these Ushnos that are located in parts lifted of the mountain range, and they are very associated to pre-Hispanic roads that they penetrate toward the river jungle Apurimac.